THE EFFECTS OF RAINFALL AND OTHER WEATHER PARAMETERS ON COCOA PRODUCTION IN NIGERIA - Lawal, Justina Oluyemisi; Omonona, Bolarin Titus (Comunicata Scientiae, 2014)
Cocoa is an important crop to Nigeria, as important as it is, the climatic factors affecting it's production cannot be controlled by human efforts. The effect of changing climate all over the world is also affecting the yield of cocoa in Nigeria. This study determines the effects of rainfall, temperature and relative humidity on Cocoa yield in Nigeria by analyzing the trend over three decades 1980-2011. The study made use of the annual readings of the three climatic parameters in question and the cocoa yield recorded over these periods. Data were subjected to inferential statistics and regression analysis in Stata. The results showed that the mean rainfall value over the three decades ranged from 1148.84 +_438.59mm, 1245.25 +_209.59 mm and 1186.27 +_175.02mm for period between 1980-1990, 1991-2000 and 2001-2011 respectively. While the yield ranged from 13.85 tons, 10.53tons and 14.21 tons; the temperature ranged from 24.64, 25.91 and 25.1oC while relative humidity also ranged between 74.91, 74.18 and 75.1% respectively in the decades. Regression of yield against rainfall shows negative correlation of 0.0067852, with temperature and relative humidity there exists positive correlations of 1.092 and 0.7346respectively. The study concluded that excessive rainfall decreases yield of cocoa, while increases in temperature and relative humidity boosts some physiological processes for pod production in Cocoa. The study recommends that farmers should adopt newly developed Cocoa varieties from Cocoa Research Institute of Nigeria which are well adapted to beat the vagaries of weather changes being experienced for improved income and livelihood.